Gendered time use during COVID-19 among adolescents and young adults in Nairobi, Kenya. (July 2022) - Williams, Anaise; Wood, Shannon N.; Stuart, H.Colleen; Wamue-Ngare, Grace; Thiongo, Mary; Gichangi, Peter; Devoto, Bianca; Decker, Michele R.
Summary: Background: Gender disparities in time use contribute to poor outcomes in women. Large-scale disruptions can affect time use. The objectives of this study were to characterize time use across the pandemic by gender and to assess how gender associates with 2021-time use, overall and by 2020 economic dependency status. Methods: A prospective cohort of youth in Nairobi, Kenya, completed phone-based surveys in August-October 2020 and April-May 2021. Time use was characterized at both time points and 1, 777 participants with complete time use data at both time points were included in the analysis. 2021-time use was regressed on gender and stratified by 2020 economic dependency status. Findings: At both time points, significant gender differences in time use found young men with more time on paid work and less time on domestic work [1·6 h; 95% CI: 1·1, 2·2] and [-1·9 h; 95% CI: -1·1, -1·5], respectively; 2021. In adjusted models, the gender differential in unpaid domestic work were significant overall and at all levels of economic dependency (dependent, semi-dependent, independent). The gender differential in paid work was evident among semi-dependent and independent. Interpretation: Young women spent less time on paid work and more time on domestic duties than male counterparts, consistently across a six-month period during the pandemic, suggesting gendered time poverty. Resulting gendered gaps in earnings can contribute to women's longer-term economic vulnerability. Funding: This work was supported by the Bill & Melinda Gates Foundation [010481].